2012
DOI: 10.1002/chem.201103663
|View full text |Cite
|
Sign up to set email alerts
|

Excess‐Electron Injection and Transfer in Terthiophene‐Modified DNA: Terthiophene as a Photosensitizing Electron Donor for Thymine, Cytosine, and Adenine

Abstract: Excess-electron transfer (EET) in DNA has attracted wide attention owing to its close relation to DNA repair and nanowires. To clarify the dynamics of EET in DNA, a photosensitizing electron donor that can donate an excess electron to a variety of DNA sequences has to be developed. Herein, a terthiophene (3T) derivative was used as the photosensitizing electron donor. From the dyad systems in which 3T was connected to a single nucleobase, it was revealed that (1) 3T* donates an excess electron efficiently to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 56 publications
3
33
1
Order By: Relevance
“…Considering results reported by the Table S1 and Figure S5 (IRF = instrument response function; Fl. [14] Lewis et al reported rate constants of 1.7 10 8 -3.7 10 10 s À1 for the bridge-mediated electron transfer in hairpin DNA sequences. research group of Wagenknecht, therefore, the CS state cannot be formed by electron transfer from dUC À in the CIP state to AQ because of the hemiprotonated C:C + base pairs of i-motif DNA.…”
mentioning
confidence: 99%
“…Considering results reported by the Table S1 and Figure S5 (IRF = instrument response function; Fl. [14] Lewis et al reported rate constants of 1.7 10 8 -3.7 10 10 s À1 for the bridge-mediated electron transfer in hairpin DNA sequences. research group of Wagenknecht, therefore, the CS state cannot be formed by electron transfer from dUC À in the CIP state to AQ because of the hemiprotonated C:C + base pairs of i-motif DNA.…”
mentioning
confidence: 99%
“…On the other hand, we found that the two block DNA hairpins, which include A:T and G:C base pairs as well as 2T, exhibited a long-lived charge-separated state indicative of C-to-C hopping on the order of 10 9 -10 10 s -1 (5-10 in Fig. 3) [54,55]. Determination of an accurate rate constant is in progress, and DNA structure dependence of the hopping rate is another important subject to be clarified.…”
Section: Eet Dynamics In Dnamentioning
confidence: 86%
“…By using bithiophene (2T) as a photosensitizing electron donor against nucleobase (T, C, A, and G), free energy changes of -0. 16 [54,55]. The charge separation process between the singlet-excited 2T and the nucleobase in the dyad system (Fig.…”
Section: Excess Electron Injection To Dnamentioning
confidence: 99%
“…6. 52,53 An ethylenedioxy-substituent was introduced to some oligothiophenes, because it has been reported that the oligomers of ethylenedioxythiophene (EDOT) showed higher electron donor-ability than those of non-substituted oligothiophenes. 54 Charge injection from the singlet excited oligothiophenes to the nucleobases was indicated by the fluorescence quenching, and confirmed by the transient absorption measurements during femtosecond laser flash photolysis.…”
Section: Excess Electron Transfer In Dnamentioning
confidence: 99%
“…, DPA. 53 Furthermore, for the observation of the excess electron hopping process within the time window possible with our current instrument, rather short DNA dumbbells including a few nucleobases were examined (Fig. 8a).…”
Section: Excess Electron Transfer In Dnamentioning
confidence: 99%